0239 Perceptions of Sleep Health among Black Americans: Recommendations for Improving Sleep - Johnson, Dayna; Smith-Ireland, Daekiara; Enun, Bassey; Barber, Lauren (Sleep (New York, N.Y.), 2023)
Introduction Despite African Americans having a high prevalence of poor sleep health, the determinants remain understudied. Sleep disparities research mainly examines quantitative data, with little attention to qualitative data, which can inform targeted interventions. We aimed to qualitatively identify 1) perceptions of sleep; 2) facilitators/barriers to healthy sleep; and 3) preferences for receiving sleep recommendations in a socioeconomically diverse sample of African Americans. Methods Participants (N=36 individuals divided into 11 groups) attended online focus groups and discussed the following topics: attitudes and beliefs about sleep, facilitators and barriers to sleep, and knowledge and attitudes about sleep recommendations. Self-reported sleep was measured via the Pittsburgh Sleep Quality Index. The focus group data were analyzed using a rapid analytic approach. Results The sample had a mean age of 34 (13.1), and 64% identified as female. The overall prevalence of poor sleep quality, short sleep duration, and long sleep duration was 39%, 24%, and 15%, respectively. Participants defined healthy sleep as a matter of quality over quantity and waking up feeling well-rested. Women, men, and gender non-conforming individuals reported average sleep durations of 6.3 hours, 5.9 hours, and 8 hours, respectively. Women, but not men or gender non-confirming individuals reported disturbed mood because of poor sleep. Regardless of gender, participants reported anxiety, stress, and daily responsibilities such as work, taking care of family, and sudden changes in plans as barriers to healthy sleep. A subset of respondents (25.5%) reported screen time and feeling unsafe as barriers. Men and women reported listening to music, aromatherapy, relaxing, and limiting phone use before bedtime as facilitators to healthy sleep. Men preferred information on how to achieve and maintain deep/quality sleep, whereas women preferred more personalized information on sleep and the sleep-mental/physical health relation. Social media was generally the preferred avenue for receiving sleep recommendations. Conclusion Mood, stress, screen time and lack of safety were identified barriers to healthy sleep patterns. Participants were interested in strategies for improving sleep health. Future studies should consider targeting relaxing bedtime routines and enhanced safety as sleep interventions. Support (if any) National Institutes of Health, National Institute for Heart Lung and Blood 1R01HL157954 and K01HL138211.